The child-nature-time relationship-New challenges for special education in the 21st century – study report - GODAWA, JOANNA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Joanna Godawa, The child-nature-time relationship-New challenges for special education in the 21st century – study report. Interdisciplinary Contexts of Special Pedagogy, no. 27, Poznań 2019. Pp. 83–98. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI: https://doi.org/10.14746/ikps.2019.27.04 The objective of the article is to show an individual’s relationship with nature in the context of the nature deficit disorder. In light of the limited volume of Polish studies concerning children and nature, the author had conducted a study concerning the relationship between children with special education needs and nature. The research shown in this article is part of a broader study conducted by the author of the article and concerning the nature deficit disorder.